2013
DOI: 10.2460/ajvr.74.1.84
|View full text |Cite
|
Sign up to set email alerts
|

Serum cobalamin and methylmalonic acid concentrations in dogs with chronic gastrointestinal disease

Abstract: These data indicated the prevalence of hypocobalaminemia in dogs with chronic gastrointestinal disease was 20 of 56 (36%). Five of 20 (25%) hypocobalaminemic dogs had increased serum MMA concentrations, which indicated that although hypocobalaminemia was common in these dogs, it did not always appear to be associated with a deficiency of cobalamin on a cellular level. Hypocobalaminemia is a risk factor for negative outcome in dogs with chronic gastrointestinal disease and should be considered in every patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 16 publications
3
59
1
3
Order By: Relevance
“…Thus, increased MMA production is a useful marker for cobalamin deficiency at the cellular level as a result of cobalamin malabsorption, decreased cobalamin transport, or both 53, 54. Concentrations of MMA can be determined in serum and urine samples,49, 53, 54 and measurement of both serum cobalamin and serum or urine MMA appears to be superior to serum cobalamin concentration alone for proper assessment of cobalamin status in dogs. However, measurement of MMA currently is not routinely performed in companion animals51 because of the cost and technical difficulty of the assay, but it might be a reasonable future strategy.…”
Section: Biomarkers In Chronic Inflammatory Enteropathies Of Dogsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, increased MMA production is a useful marker for cobalamin deficiency at the cellular level as a result of cobalamin malabsorption, decreased cobalamin transport, or both 53, 54. Concentrations of MMA can be determined in serum and urine samples,49, 53, 54 and measurement of both serum cobalamin and serum or urine MMA appears to be superior to serum cobalamin concentration alone for proper assessment of cobalamin status in dogs. However, measurement of MMA currently is not routinely performed in companion animals51 because of the cost and technical difficulty of the assay, but it might be a reasonable future strategy.…”
Section: Biomarkers In Chronic Inflammatory Enteropathies Of Dogsmentioning
confidence: 99%
“…However, measurement of MMA currently is not routinely performed in companion animals51 because of the cost and technical difficulty of the assay, but it might be a reasonable future strategy. Serum MMA concentrations can be increased in patients with renal insufficiency49 and must be interpreted in light of the serum creatinine or symmetric dimethylarginine (SDMA) concentration.…”
Section: Biomarkers In Chronic Inflammatory Enteropathies Of Dogsmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Cobalamin deficiency in dogs is commonly associated with canine CE with a reported prevalence of 6-73%. [9][10][11][12][13] Hypocobalaminemia has also been reported to be a negative prognostic factor in dogs with CE or EPI, associated with an increased risk of euthanasia. 9,14 Suggested mechanisms of cobalamin deficiency in canine CE are damage to the ileal mucosal receptors for binding of cobalamin-intrinsic factor (IF) complexes or bacterial competition for nutrients in small intestinal dysbiosis resulting in decreased amounts of cobalamin available for absorption.…”
mentioning
confidence: 99%
“…Cobalamin is necessary for the methylmalonyl CoA mutase (MCM) system (Solomon, 2007) and deficiencies can result in the production of methylmalonic acid (Stabler et al, 1986). Berghoff et al (2013) showed that the prevalence of hypocobalaminaemia in dogs with CE was 36%, while a quarter of these dogs had increased levels of methylmalonic acid. It has been recommended that all dogs showing signs of chronic gastrointestinal disease should have cobalamin levels assessed (Dossin, 2011).…”
Section: Appraisal Application and Reflectionmentioning
confidence: 99%